Mental Well-Being Related To Lifestyle and Risky Behaviours in 18-25 Year Old: Evidence from North-East Scotland. - Lorna, Aucott; Amudha, Poobalan; Mary, McCallum; W, Cairns S Smith (Universiti Kebangsaan Malaysia, 2014)
This study assesses the mental well-being of young adults (18-25 year olds),a recognized weight gain time period, in relation to self-reported weight, diet, physical activity and other risky lifestyle behaviours.